A new species of the genus Cryptotendipes Beck et Beck, 1969 (Diptera: Chironomidae) from India, with a world key to the males and tentative phylogenetic relationship - Mukherjee, Bindarika; Mukherjee, Tuhar; Hazra, Niladri (Zootaxa, 2020)
A new species of the genus Cryptotendipes Beck et Beck is described on the basis of adult male. It is the third species from India and ninth from the Oriental region. The Chinese species, C. nodus Yan, Tang et Wang, 2005 is recorded firstly from India. The molecular barcoding of two species, Cryptotendipes disparilis Pal et Hazra, 2018 and C. nodus is provided. Additional information and revision of two Indian species Cryptotendipes aculeatus Pal et Hazra, 2018 and C. disparilis Pal et Hazra, 2018 are furnished for erroneous description. A tentative cladistic relationship based on the morphological data of adult males and a revised world key to the adult males of the genus Cryptotendipes are also provided.